The simple geometry of transmission and stabilization in closed and open economies - Giancarlo Corsetti; Paolo A. Pesenti (Federal Reserve Bank of New York, 2005)
This paper provides an introduction to the recent literature on macroeconomic stabilization in closed and open economies. We present a stylized theoretical framework, illustrating its main properties with the help of an intuitive graphical apparatus. Among the issues we discuss are optimal monetary policy and the welfare gains from macroeconomic stabilization, the international transmission of real and monetary shocks and the role of exchange rate pass-through, and the design of optimal exchange rate regimes and monetary coordination among interdependent economies
Keywords: E31; E52; F42; 330; Geldpolitik; Exchange Rate Pass-Through; Offene Volkswirtschaft; Ökonometrisches Modell